Legal Protection Orientation And Formulation For Traditional Musical Instruments As Patents: An Inclusive Legal Paradigm - Kurniawan, I Gede Agus; Lulo, Lourenco de Deus Mau (Faculty of Law, Universitas Jenderal Soedirman, 2023)
One of the consequences of the extinction of several traditional musical instruments in Indonesia is the reduction in traditional musical instrument craftsmen because the manufacture of traditional musical instruments does not guarantee a substantive economic increase for the craftsmen. Therefore, legal action is needed so that traditional musical instruments can have an economic orientation and implications for the craftsmen so that they can become an important factor in preserving traditional musical instruments in Indonesia. This study aims to orient the legal protection of traditional musical instruments through patents in an inclusive legal perspective. This research is a normative legal research with a concept and statutory approach. The results of the study confirm that the legal protection orientation of traditional musical instruments as patents can be carried out by qualifying traditional musical instruments as simple patents. Internal legal protection is carried out by classifying traditional musical instruments as simple patents, must be accompanied by awareness and understanding of every traditional musical instrument craftsman to be able to register patents, besides that externally, the state needs to provide convenience, facilitation and incentives for traditional musical instruments as simple patents including making certain legal breakthroughs and policies by providing formulations regarding affirmative action legal policies related to efforts to register traditional musical instruments in an inclusive legal perspective that needs to be implemented so as to provide facilitation as well as empowerment for traditional musical instruments to be registered as simple patents.